Regrowth age of Erythrina americana Miller and concentration of phenolic compounds in the foliage - Hernández-Espinoza, Diana Fabiola; Lagunes-Espinoza, Luz del Carmen; López-Herrera, María Aurelia; Ramos-Juárez, Jesús Alberto; González-Garduño, Roberto; Oliva-Hernández, Jorge (Instituto de Ecología, A.C., 2020)
The foliage of some trees can be used for feeding small ruminants, when the chemical quality and the content of secondary metabolites are suitable. The use of Erythrina americana as feed requires knowledge of its nutritional composition at different regrowth ages. The objective of the study was to determine the influence of the regrowth age of E. americana on the content of phenolic compounds and chemical composition of the foliage, from 24 trees that are part of the live fences of a sheep farm. A completely randomized design was used; the fixed factor was the regrowth age of E. americana (60 days, 90 days and 120 days). The response variables were: dry matter, crude protein, ash, organic matter, neutral detergent fiber, acid detergent fiber, total polyphenols, non-tannin phenols, condensed tannins, hydrolysable tannins and total tannins. The regrowth age affected (P < 0.05) the content of crude protein, structural carbohydrates, total polyphenols and tannins (condensed, hydrolysable and total); the rest of the variables was not affected (P> 0.05). At 90 days, the highest crude protein content was detected. The lowest structural carbohydrates content was between 90 days and 120 days. As the regrowth age increased, a higher condensed tannins concentration was detected. Crude protein, condensed tannins and structural carbohydrates in foliage of E. americana, at an age of regrowth of 90 days, allow to consider it as a complementary food for small ruminants.